Desenvolvimento de procedimentos metodológicos na prospecção de microalgas propícias para a produção de biodiesel - Pepino, Rodrigo Fernando (2011)
The chemical compounds called triacylglycerides (TAGs) have been the main source for biodiesel. The isolation of high lipid yield microalgae is important for the success of algae biomass production for biodiesel and, therefore, a search not only for organisms that fulfill such profile, but also for techniques effective in rapid lipid detection is fundamental. A number of methodologies on the characterization of microalgae lipid production, such as FTIR and RMN spectroscopy and spectrofluorimetry using the Nile Red dye are presented in this study. The Fourier Transform Infrared Spectroscopy (FTIR) technique have been largely used in biological system studies due to its rapid analysis, no pretreatment data gathering and easy biochemical characterization of intact cells. This study proposes a technical optimization of the FTIR technique for microalgae usage purposes as a practical approach for concomitantly prospecting large amounts of microalgae species with focus on biodiesel production. The Red Nile fluorescence has been successfully applied in microalgae lipid determination. In this research, the lipid (neutral) amount was determined by fluorescence in 430-570nm and a linear correlation established with the data gathered through gravimetry. After prospecting a number of species from the laboratory s stock cultures, the freshwater microalgae Scenedesmus sp (Clone MJ13) has been selected for study under traditional growth practices and under conditions of different nitrogen and phosphorus concentrations. The results showed a fast metabolic answer of Scenedesmus sp to the nutritional availability and the efficiency of the FTIR spectroscopy as a fast and reliable method for the determination of lipid production in a prospecting process.